Application of micro/nano technology for thermal management of high power LED packaging – A review. (25th December 2018) - Hamidnia, M.; Luo, Y.; Wang, X.D.
Highlights: Study thermal conductivity of LED packaging: die, submount and carrier substrate. Material-based and micro/nano technology-based thermal solutions. Preference of COB array to SMT in high power LED packaging with small size. Significant potential of Si to use as a carrier substrate. High conductive thermal interface materials with adding nano powder. Abstract: With technological progress, the request for high power LEDs (HP-LEDs) as a replacement candidate for common lamp is increased. Due to dissipation of 70–85% of LED input power in form of heat, thermal management of LED packaging is unavoidable. A review of the literature related to thermal management of HP-LED based on the different materials and fabrication methods are used in LED packaging structure to provide a concise overview of the recent advances in this field of study. In this paper, different materials of LED packaging through the heat dissipation path, from LED chip until heat sink are evaluated by details. The state-of-the-art of micro/nano technology-based thermal solutions for three levels of (a) LED chip, (b) submount, and (c) carrier substrate are addressed. The fundamental of introduced thermal management solutions are material-based and fabrication-based solutions.